2019
DOI: 10.1111/adb.12831
|View full text |Cite
|
Sign up to set email alerts
|

Interoceptive attention in opioid and stimulant use disorder

Abstract: Blunted anterior insula activation during interoceptive perturbations has been associated with stimulant (cocaine and amphetamine) use disorder (SUD) and is related to risk for and prognosis of SUD. However, little is known whether these interoceptive alterations extend to opioid use disorder (OUD). This exploratory study used the same experimental probe during functional magnetic resonance imaging (fMRI) to test the hypothesis that SUD and OUD exhibit interoceptive discrepancies characterized by subjective ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
46
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
4
2

Relationship

3
7

Authors

Journals

citations
Cited by 52 publications
(46 citation statements)
references
References 49 publications
0
46
0
Order By: Relevance
“…While the literature on interoceptive dysfunction is mixed for anxiety disorders broadly, it is well-stablished in panic disorder (reviewed in [6]). A couple recent studies have also reported evidence of differences in interoceptive processing in both SUDs (e.g., blunted brain responses [7]) and eating disorders (e.g., stronger effects of prior beliefs on perception during low arousal [8]). The computational framework within which our findings were observed is also in line with several recent proposals about the role of interoceptive inference in guiding (predictive) autonomic control and the potential breakdown of this mechanism within different psychiatric conditions [10-15, 36, 38]; however, in contrast to previous emphasis on altered prior beliefs in these proposals, our results more selectively support the existence of deficits in adjusting precision estimates for afferent interoceptive signals-and do not provide strong support for the presence of altered priors.…”
Section: Differences In Interoceptive Precisionmentioning
confidence: 98%
“…While the literature on interoceptive dysfunction is mixed for anxiety disorders broadly, it is well-stablished in panic disorder (reviewed in [6]). A couple recent studies have also reported evidence of differences in interoceptive processing in both SUDs (e.g., blunted brain responses [7]) and eating disorders (e.g., stronger effects of prior beliefs on perception during low arousal [8]). The computational framework within which our findings were observed is also in line with several recent proposals about the role of interoceptive inference in guiding (predictive) autonomic control and the potential breakdown of this mechanism within different psychiatric conditions [10-15, 36, 38]; however, in contrast to previous emphasis on altered prior beliefs in these proposals, our results more selectively support the existence of deficits in adjusting precision estimates for afferent interoceptive signals-and do not provide strong support for the presence of altered priors.…”
Section: Differences In Interoceptive Precisionmentioning
confidence: 98%
“…All participants provided written informed consent before they completed the study protocol, in accordance with the Declaration of Helsinki, and they were compensated for participation (ClinicalTrials.gov identifier NCT02450240). A number of previous papers have been published from the larger T1000 data set, [36][37][38][39][40][41][42][43][44][45][46] but none of these papers has included analyses or data from the AAC task.…”
Section: Participantsmentioning
confidence: 99%
“…ClinicalTrials.gov identifier: #NCT02450240. For previous papers published from the larger T1000 dataset, see [27][28][29][30][31][32][33][34][35][36][37] . With the exception of our previous paper 20 , none of these papers included analyses using the AAC task.…”
Section: Participantsmentioning
confidence: 99%